A novel green method for deproteinization of polysaccharide from Cipangopaludina chinensis by freeze-thaw treatment. (20th January 2017) - Xiong, Qingping; Huang, Song; Chen, Jianhui; Wang, Baolan; He, Lian; Zhang, Lei; Li, Shijie; Wang, Jizhong; Wu, Jianguo; Lai, Xiaoping; Zhang, Danyan
Abstract: The purpose of this paper was to develop a green method for deproteinization of polysaccharide (PCC) from Cipangopaludina chinensis by freeze-thaw treatment (FTT). Based on single-factor experiments of FTT, firstly, the optimal deproteinization parameters of PCC were obtained by comparing their deproteinization ratio ( D r %), recovery ratio ( R r %) and selectivity coefficient ( K c ) as follows: freezing temperature of −40 °C, freezing time of 96 h, thawing temperature of 10 °C and freeze-thaw cycles of 11 times. Under optimal conditions, The D r %, R r % and K c of PCC were 87.10 ± 1.91%, 84.91 ± 2.45% and 5.77 ± 0.43, respectively. Then, the deproteinization performance of FTT for PCC under optimal conditions was compared with the most typical Sevage method. We found that there were no significant differences between FTT and Sevage method on the D r %, monosaccharide composition, characteristic group and molecular weight degradation. However, compared with Sevage method, FTT not only had higher R r % and K c, but also were non-pollution. The results demonstrated that FTT would be a promising and green method for deproteinization of PCC. Graphical abstract: Highlights: Freeze-thaw treatment (FTT) was used to remove protein impurities of polysaccharides. FTT had unique superiority of green non-pollution for deproteinization. FTT was suited to deproteinization of polysaccharide from Cipangopaludina chinensis. FTT might be able to replace the most typical Sevage method for deproteinization.